2011
DOI: 10.1017/s0031182011000503
|View full text |Cite
|
Sign up to set email alerts
|

MixedTheileriainfections in free-ranging buffalo herds: implications for diagnosingTheileria parvainfections in Cape buffalo (Syncerus caffer)

Abstract: S U M M A R YBuffalo-adapted Theileria parva causes Corridor disease in cattle. Strict control measures therefore apply to the movement of buffalo in South Africa and include mandatory testing of buffalo for the presence of T. parva. The official test is a realtime hybridization PCR assay that amplifies the V4 hypervariable region of the 18S rRNA gene of T. parva, T. sp. (buffalo) and T. sp. (bougasvlei). The effect that mixed T. parva and T. sp. (buffalo)-like infections have on accurate T. parva diagnosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 34 publications
3
53
1
Order By: Relevance
“…It also implies that the specific parasitaemia range of a species may determine its practical LOD. As such, >95% of the T. parva population in African buffalo have parasitaemias >0.00001%, which is well above the determined detection limit (Pienaar et al., 2011a). The same holds for T. sp.…”
Section: Sensitivity Of Molecular Assays Carrier State and Parasitaementioning
confidence: 58%
See 1 more Smart Citation
“…It also implies that the specific parasitaemia range of a species may determine its practical LOD. As such, >95% of the T. parva population in African buffalo have parasitaemias >0.00001%, which is well above the determined detection limit (Pienaar et al., 2011a). The same holds for T. sp.…”
Section: Sensitivity Of Molecular Assays Carrier State and Parasitaementioning
confidence: 58%
“…Sensitivity of the RLB is severely affected by the fact that universal primers are used and these are depleted by the predominant species present, thereby suppressing the signal from less abundant template (Pienaar et al., 2011a). The sensitivity of the hybridisation assay for T. parva (Sibeko et al., 2008) is similarly affected by the presence of T. sp.…”
Section: Sensitivity Of Molecular Assays Carrier State and Parasitaementioning
confidence: 99%
“…Theileria sp. (buffalo) was found in African buffalo in Uganda, Kenya and southern Africa, with no substantive reports that cattle can be infected (Oura et al 2004(Oura et al , 2011Pienaar et al 2011a). Theileria sp.…”
Section: Discussionmentioning
confidence: 99%
“…(buffalo) and T. sp. (bougasvlei) was subsequently shown to be present in buffalo from southern Africa, to be apathogenic and has not yet been found in cattle (Allsopp et al 1999;Oura et al 2004Oura et al , 2011Mans et al 2011a;Pienaar et al 2011a). Theileria sp.…”
Section: Introductionmentioning
confidence: 99%
“…The brown ear ticks Rhipicephalus appendiculatus, R. duttoni and R. zambeziensis are considered to be the main vectors of T. parva, which causes East Coast fever, CD and January disease in cattle [17,18]. CD results when buffalo derived T. parva is transmitted via ticks from buffalo to cattle, which results in mortality, although evidence has shown that cattle that survive this infection then go on to become immune to it [19][20][21][22]. Indeed, Yusufmia et al (2010) [23] found evidence that suggests that cattle may also be subclinical carriers of T. parva.…”
Section: A Summary Of the History Of The Four Most Important Diseasesmentioning
confidence: 99%